A Descriptive Analysis of Students’ Learning Motivation in Higher Education - Nurjayanti, Nurjayanti; Susilawati, Susilawati (Journal of English Language and Education, 2025)
Understanding student motivation is essential for promoting engagement, persistence, and academic success. Motivation influences how students approach learning tasks, manage challenges, and sustain their efforts over time. This study employed a quantitative descriptive method, utilizing a survey with an 18-item online questionnaire on a five-point Likert Scale as the primary data collection instrument. The respondents were 169 higher education students in Rengat town, selected using simple random sampling. Data were analyzed descriptively, including frequency counts, percentages, mean scores, and standard deviation. The main findings indicated that most of the students’ overall motivation was categorized into "good". Sub-factors rated as "excellent" included students’ passion and desire to succeed, students’ encouragement and need for learning, students’ hopes and aspirations for the future, and students’ appreciation in learning. Sub-factors categorized as "good" were students’ interesting activities in learning and students’ conducive learning environment. The study found that most higher education students demonstrated good motivation, with several key motivational sub-factors showing excellent levels. This research offers valuable insights for educators aiming to enhance student engagement and academic success in higher education.